Detection of neuroendocrine tumour of sphenoid sinus on the Gallium-68 DOTATATE PET/CT: a rare entity - Shamim, Syed Ejaz; Khairuman, Khairul Aliff; Abdul Onny, Muhammad Adib; Mohd Yusoff, Suryati; Ahmad Saad, Fathinul Fikri (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2022)
Neuroendocrine tumours (NETs) are a category of neoplasm that is characterised by its phenotypic and heterogeneity. The occurrence of this type of neoplasm in the nasal cavity and paranasal sinuses is extremely rare accounting for only 0.2-0.8% of all cancers. NET tends to expresses somatostatin receptors (SSTR) and owning to this unique characteristic, molecular imaging has been able to detect these tumours using radiolabelled somatostatin analogue agent. Gallium-68 (Ga-68) DOTATATE PET/CT is an example of SSTR imaging and has been shown to be of importance in the assessment and staging of NET. We present a case of a rare sphenoid sinus NET in a 45-year-old gentleman whom initially presented with persistent left eye pain which led to visual loss. We described the utilization of Ga-68 DOTATATE PET/CT in the diagnosis and staging of this patient which in turn dictated treatment approach.